Public Organization as a Subject of Civil Legal Relations According to Law of Ukraine and Commonwealth of Independent States (CIS) Countries - FEDORCHENKO, Nataliia V.; SHYMON, Svitlana I.; VYSHNOVETSKA, Svitlana V.; MIKHNEVYCH, Liudmyla V.; BAZHENOV, Mikhail I. (Journal of Advanced Research in Law and Economics, 2019)
The activities of civil-society structures, an integral part of which are public associations, is one of the most important conditions for the implementation of effective socio-political and economic transformations and reforms. The issue of obtaining the status of a civil legal entity by a public organization requires further development. Common ‘inherited’ by states archaic norms of civil law of the Soviet Union, despite their successful multi-year approbation, require their qualitative renewal in the light of globalization and the implementation of European standards and requirements. The urgency of the topic is also determined by the need of Ukrainian society in effective public organizations that act as a full participant in civil legal relations, are a component of civil society and a catalyst for its growth and Europeanisation. The peculiarities of the legislative interpretation of the terms ‘public associations’ and ‘public organizations’ in Ukraine and Commonwealth of Independent States (CIS) countries were analyzed. A comparative legal analysis of the status of public organizations in Ukraine and CIS countries was conducted. The discussion position regarding the increase of the influence of public organizations on the state authorities and the management of society was reviewed. It was substantiated that the purpose of the activity of modern civil-society organizations as subjects of civil legal relations should be the long-term planning of the mechanism of realization of certain social priorities.